RELATION BETWEEN FOOD CONSUMPTION PATTERN AND DMF-T INDEX OF STUDENTS IN WETLANDS AREA OF KABUPATEN BARITO KUALA Observation on MTs students in Kabupaten Barito Kuala - Rosihan Adhani; Annisa Faradila; Widodo Widodo (Dentino : Jurnal Kedokteran Gigi, 2017)
Background: Food consumption pattern is the composition of type, and amount of food material consumed by a person or population in a particular frequency and period of time. Data taken from 2013th RISKESDAS show that 75,5% Barito Kuala citizens over 10 years old have the tendency to consume sugary foods more than once a day. The high pattern of consuming sugary foods affects the dental plaque formation on tooth surface because strongly-attached plaque has great potential to induce caries. Caries plays an important part in oral health problems in Barito Kuala. Report shows that Barito Kuala citizens over 12-year-old have high caries history, even reaching 89%. This report is supported by 2007th RISKESDAS, which states that DMF-T index of Barito Kuala is 6.61 or very high. Purpose: The purpose of this study was to assess the relation between food consumption pattern and DMF-T index of students in wetlands area of Barito Kuala. Methods: This study was quantitative analytical study using cross sectional approach. Data were collected using Food Frequency Questionnaire and DMF-T index sheets. 100 samples were chosen using cluster sampling method. Results: Data were analyzed using Spearman test with 0.001 significance (p<0.05) and strong correlation (r=-0,648). Conclusion: There was a relation between food consumption pattern and DMF-T index of students in wetlands area of Barito Kuala